2020
DOI: 10.3390/insects11120841
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Cold Stress Affects Parasitism on the Asian Chestnut Gall Wasp Dryocosmus kuriphilus

Abstract: Temperature variation affects interactions involving plants, herbivores, and parasitoids, causing a mismatch between their phenological cycles. In the context of climate change, climatic factors can undergo profound and sudden changes, such as sudden hot or cold snaps. Herein, we show that the number of episodes of short but sustained low temperatures has increased, mainly during May, over the last two decades. We subjected galls induced by the Asian chestnut gall wasp (ACGW) Dryocosmus kuriphilus to cold stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Air temperature, air humidity, elevation, and soil can be counted as determining factors for the spread of diseases and pests in the chestnut tree. The temperature variation can act on different biological and evolutionary aspects, in the hosts and parasitoids, can reveal effects on the development and death of pathogenic individuals or reduced productivity [ 31 , 48 , 49 ]. Very wet springs can be detrimental, promoting the development of ink disease ( P. cinnamomi ) and white root rot disease ( Armillaria mellea ) [ 44 ].…”
Section: Chestnut Tree and Climate Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Air temperature, air humidity, elevation, and soil can be counted as determining factors for the spread of diseases and pests in the chestnut tree. The temperature variation can act on different biological and evolutionary aspects, in the hosts and parasitoids, can reveal effects on the development and death of pathogenic individuals or reduced productivity [ 31 , 48 , 49 ]. Very wet springs can be detrimental, promoting the development of ink disease ( P. cinnamomi ) and white root rot disease ( Armillaria mellea ) [ 44 ].…”
Section: Chestnut Tree and Climate Influencementioning
confidence: 99%
“…Water and heat stress lessen plant growth and less vigor, also increasing susceptibility to biotic factors such as ink and blight diseases [ 29 ]. For some insect species, such as Mesopolobus tibialis , the population doubled when exposed to simulations of sudden stress events due to the cold temperatures (adaptive capacity) [ 49 ]. A variation in parasitism rates can be an immediate response to intraseasonal temperature variations, climate change, and variations in habitat.…”
Section: Climate Change Projections and Chestnut Growing Conditionsmentioning
confidence: 99%
“…As a result, a change in parasitism rate could be described as an instant stress response [72][73][74]. The factors that influence parasitoid species composition are difficult to identify, and the reasons why some species react to stress more effectively than others have remained unclear [75].…”
Section: Discussionmentioning
confidence: 99%
“…Ouyang et al [ 39 ] suggested that climate change and agricultural intensification of the Anthropocene could potentially induce outbreaks of many pest insects by weakening the density-dependent population regulation. Other factors are to be considered, such as those related to particular microclimatic variations or sudden hot or cold snaps [ 40 ] that have probably affected the area and that is being analyzed with new research.…”
Section: Discussionmentioning
confidence: 99%